Juventudes, apartheids e semânticas do medo: sentidos e vivências emocionais urbanas a partir da psicologia histórico-cultural - Cabral, Daniel Welton Arruda (2021)
Brazil is one of the countries with the highest homicide rates in the world, and the concentration of occurrences has been amplified in the northeastern cities, especially in the last two decades, victimizing still more younger populations and producing fear. In Fortaleza, only in the first semester of 2020, 409 teenage lives were taken. This thesis investigated the psychosocial implications of urban fears in teenagers (15 to 19 years old) in the city of Fortaleza, based on 2 cutouts: territory (center and periphery) and gender. We used a multi-method approach with the application of semi-structured interviews, a questionnaire to measure urban fears and the Generating Instrument of Affective Maps (GIAM). Several studies have been attesting to the growth of urban fears in different parts of the world, even where violence rates have been decreasing, indicating that real risk and fear are not necessarily correlated. Nevertheless, a large part of Brazilian studies explore urban fears as the exclusive consequence of violence. We find that, besides the real risks, cultural aspects have been responsible for the increase in fear, which leads to the expansion of segregation and generates apartheid in the city of Fortaleza, causing adolescents in the central and peripheral territories to find themselves practically not outside subordinate or fear relationships. Female adolescents from both territories presented an intertwining of fears of sexual, verbal, and physical violence. The male adolescents in the center manifested only fear of being assaulted and murdered, fears present in all the participating groups. Adolescents in the periphery accumulated other fears, such as being "confused" with drug factions; having someone in their family hurt; being hit by a stray bullet; by the police; and "disembarking," the last two present only in the male gender. Especially in this territory, fear has impelled some adolescents to incarcerate themselves, contributing to generating suffering such as constant crying crises; depression; deep sadness; self-mutilation; suicide attempts; mental disorganization; anxiety; intense anger crises. Although the adolescents in the periphery suffered more experiences of violence, the adolescents in the center had more anxious fears, with no definite object. Such anxiety was related to inadequate and stigmatized ideas about the residents of the periphery, ideologically reproduced and spread by a culture of fear, which produces a series of sad passions that are at the genesis of apartheid practices. The force of fear's diffusion has been shown to result from its effectiveness in expressing deep cultural anxieties. The high rates of violence in the city have led to the feeling that all city dwellers are at the same risk, which has maximized the anxiety rate of this population, amplifying movements of self-defense, producers of segregation. This has generated a cycle in which violence, segregation and fear feedback, with harmful effects, especially in the periphery, suchas disintegration of social ties and emergence of enmity relationships, producing intraperipheral apartheids, in which adolescents have been murdered just for crossing the limits of their neighborhood.